The Impact of Basic Programming Interactive E-Module Implementation on Students’ Learning Outcomes in Distance Learning - Samala, Agariadne Dwinggo; Ambiyar; Sukardi; Indarta, Yose; Ranuharja, Fadhli (Politeknik Ganesha Medan, 2022)
This study aims to identify the implications of implementing an interactive e-module for learning basic programming in distance learning. The subject of this research were students of Informatics Education Study Program, Department of Electronic Engineering, Universitas Negeri Padang. This research was carried out in the odd semester of 2020/2021 academic year. This research used an experimental method using a quantitative approach with a posttest-only control group design. The sampling technique used purposive sampling. In the results of the midterm exam, it is known that the learning outcomes students from the control group without treatment obtained the lowest score of 64.00; highest score 84.00; an average of 75.27; while students from the experimental group with interactive e-modules obtained the lowest score of 76.00; highest score 96.00; with an average of 84.83; Furthermore, the results of the final exam obtained student learning outcomes from the control group without treatment, the lowest score was 60,00; highest score 82,00; with an average of 72.07; while student learning outcomes from the experimental group obtained the lowest score of 72,00; highest score 90,00; with an average of 81.60. The results showed that the learning outcomes of the experimental group are much better than the learning outcomes of the control group. It means that there is a significant effect of using distance learning interactive e-module on learning outcomes of basic programming.